2006
DOI: 10.1111/j.1743-6109.2006.00162.x
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic validity of three swab techniques for identifying chronic wound infection

Abstract: This study examined the diagnostic validity of three different swab techniques in identifying chronic wound infection. Concurrent swab specimens of chronic wounds were obtained using wound exudate, the Z-technique, and the Levine technique, along with a specimen of viable wound tissue. Swab and tissue specimens were cultured using quantitative and qualitative laboratory procedures. Infected wounds were defined as those containing 1 x 10(6) or more organisms per gram of tissue. Accuracy was determined by associ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
147
2
4

Year Published

2007
2007
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 153 publications
(159 citation statements)
references
References 14 publications
2
147
2
4
Order By: Relevance
“…Our method of ulcer fluid sampling, from the reproducible CFU counts from the same wound, and others (13) have also shown that postdebridement wound fluid CFU highly correlates with CFU counts derived from tissue samples in the same wound.…”
Section: Results -supporting
confidence: 59%
“…Our method of ulcer fluid sampling, from the reproducible CFU counts from the same wound, and others (13) have also shown that postdebridement wound fluid CFU highly correlates with CFU counts derived from tissue samples in the same wound.…”
Section: Results -supporting
confidence: 59%
“…The essential oils of four Ocimum species grown in Rwanda have been shown to possess antimicrobial activity against Escherichia coli, Bacillus subtilis, Staphylococcus aureus and Trichophyton metagrophytes (Janssen et al, 1989). It is probable that the antimicrobial activity of the oils from O. suave may be helpful in keeping away microor-ganisms especially S. aureus which is a major bacterial burden in chronic wounds (Gardner et al, 2004) and therefore enhance wound healing. The plant extracts left no prominent scar at the wound sites while neomyicin sulfate treated groups had prominent scars.…”
Section: Discussionmentioning
confidence: 99%
“…23,24 Most studies of quantitative bacterial cultures in chronic wounds have not associated microbial load with healing outcomes. [25][26][27] Two exceptions include Davies et al 23 and Lantis et al 24 Davies et al prospectively performed quantitative tissue biopsies and surface swabs of 66 patients with clinically noninfected chronic VLUs at baseline and monitored healing outcomes. They showed that neither quantitative tissue biopsy (CFU/g) nor surface swabs (CFU/mL) of the wound at baseline predicted healing at 6 months in a logistic regression model.…”
Section: Microbial Loadmentioning
confidence: 99%
“…Overall, cultivation methods have been shown to be comparable between biopsies and swabs for aerobes, although there are more discrepancies for anaerobes and overall quantities of bacteria, suggesting uneven vertical distribution of at least some species as discussed in the Intra-and Interwound Variation section. 23,25,37,40 Molecular-based studies performed to date have predominantly used sharp debridement samples without comparison of different sampling methods or indication of the depth of the wound sampled.…”
mentioning
confidence: 99%